Faktor Internal Dan Eksternal Yang Mempengaruh Audit Report Lag - Fenny Budi Utami; Irianing Suparlinah; Agus Faturokhman (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the effect of profitability, solvency, company size, company age, audit opinion, and KAP reputation on audit report lag. The object of this research is mining companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The method used in this study is quantitative and the data source used is secondary data. The sample in this study were mining companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The sampling technique in this study used a purposive sampling method. The data analysis used in this study is multiple linear regression analysis. The results of this study indicate that (1) profitability, solvability, company size, company age, audit opinion, and KAP reputation simultaneously had a significant effect on audit report lag; (2) profitability has a negative effect on audit report lag; (3) solvency has a positive effect on audit report lag; (3) company size does not negatively affect audit report lag; (4) company age negatively affects audit report lag; (5) audit opinion does not negatively affect audit report lag (6) KAP reputation does not negatively affect audit report lag; (7) audit opinion does not have the most dominant influence on audit report lag.